Checklist for a complete chronic urticaria medical history: an easy tool - Cherrez-Ojeda, Iván; Cherrez, Sofia; Colbatzky, Florian; Cherrez, Annia (World Allergy Organization journal, 2017)
Existing guidelines do not offer a quick, efficient alternative to the patient’s recollection of relevant clinical features during anamnesis and physical examination for chronic urticaria (CU). This study aimed to identify specific items reflecting the main characteristics of CU that should be included in a comprehensive medical history for patients with CU. We also aimed to clarify possible eliciting factors for CU to support accurate diagnosis of the disease.